Step-by-step explanation:
[tex] \tt{9 {x}^{2} - 12x + 4}[/tex]
Here, the second order of polynomial ax² + bx + c is factorized and expressed as the product of two linear factors. First, we have to find the two numbers that adds to 12 and if we multiply those numbers , we get 36 ( The two numbers should be 6 and 6 ).
⟶ [tex] \tt{9 {x}^{2} - (6 + 6)x + 4}[/tex]
⟶ [tex] \tt{9 {x}^{2} - 6x - 6x + 4}[/tex] { Distribute x through the parentheses )
⟶ [tex] \tt{ \underbrace{9 {x}^{2} - 6x}} \: - \underbrace{6x + 4}[/tex]
⟶ [tex] \tt{3x(3x - 2) - 2(3x - 2)}[/tex]
⟶ [tex] \tt{(3x - 2)(3x - 2)}[/tex]
⟶ [tex] \tt{ {(3x - 2)}^{2} }[/tex]
[tex] \pink{ \boxed{ \boxed{ \tt{ Our \: final \: answer : \boxed{ \underline{ \tt{{(3x - 2)}^{2} }}}}}}}[/tex]
Hope I helped ! ♡
Have a wonderful day / night ! ツ
▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁